2018
DOI: 10.6061/clinics/2018/e373
|View full text |Cite
|
Sign up to set email alerts
|

Acute blood pressure responses after different isometric handgrip protocols in hypertensive patients

Abstract: OBJECTIVE:The present study analyzed blood pressure responses after a single session of isometric handgrip exercise performed with different volumes and intensities by patients with hypertension.METHODS:This randomized crossover trial submitted 12 hypertensive patients (58±5 years old) to four isometric handgrip exercise sessions in a random order: 4 x 2 min at 30% of the maximal voluntary contraction (S30%); 4 x 2 min at 50% of the maximal voluntary contraction (S50%2min); 4 x 3 min at 30% of the maximal volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
4
15
1
9
Order By: Relevance
“…Sex (male/female) dictory findings [17][18][19][20]. Similar to our results, Olher et al [17] did not find a reduction in resting BP up to 60 min following isometric handgrip exercise sessions (4 × 5 contractions of 10 s at 30 and 50 % of maximal voluntary isometric contraction; MVIC) in older females with hypertension.…”
Section: Mean ± Sdsupporting
confidence: 91%
See 2 more Smart Citations
“…Sex (male/female) dictory findings [17][18][19][20]. Similar to our results, Olher et al [17] did not find a reduction in resting BP up to 60 min following isometric handgrip exercise sessions (4 × 5 contractions of 10 s at 30 and 50 % of maximal voluntary isometric contraction; MVIC) in older females with hypertension.…”
Section: Mean ± Sdsupporting
confidence: 91%
“…As pointed out in the methods section, we prescribed the 4 × 1 min and not 4 × 2 min as the traditional isometric handgrip exercise protocol, because of the participants' tolerance and safety regarding the respiratory pattern and to avoid the Valsalva maneuver. Nonetheless, the non-occurrence of PEH up to 30 min post-exercise is similar to what has previously been observed in isometric handgrip exercise protocols, even using a higher volume of contractions (i. e., 8 min or 12 min) [17][18][19]. These studies used isometric handgrip exercise sets from 1 to 3 min, which suggests that the duration of contractions does not play a role in PEH when small muscle groups are involved in isometric exercise protocols.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Pedoman pengobatan Eropa dan AS merekomendasikan modifikasi gaya hidup sebagai terapi non farmakologis, salah satunya adalah peningkatan aktivitas fisik melalui terapi Isometric Handgrip Exercise (Okamoto et al, 2019). American Heart Association (AHA), mengklasifikasikan terapi Isometric Handgrip Exercise sebagai terapi potensial untuk menurunkan tekanan darah pada pasien hipertensi (Silva et al, 2018).…”
Section: Pendahuluanunclassified
“…Badrov et al (2013) did not report any adverse events after 8 weeks of training. Studies have observed a modest increase in heart rate (Δ = 3 ± 4 bpm), systolic blood pressure (Δ = 16 ± 10 mm Hg) and diastolic blood pressure (Δ + 7 ± 6 mm Hg) during isometric exercise (Araujo et al, 2011), as well as no significant changes after the exercise (Farah et al, 2017;Silva et al, 2018;Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%